Poly(2-oxazoline)-based magnetic hydrogels: Synthesis, performance and cytotoxicity - Cvek, Martin; Zahoranova, Anna; Mrlik, Miroslav; Sramkova, Petra; Minarik, Antonin; Sedlacik, Michal (Colloids and surfaces, B, Biointerfaces, 2020)
[Display omitted] •Magnetic hydrogels based on poly(2-ethyl-2-oxazoline) (POx) were fabricated.•The effects of magnetic content on structural and functional behaviour were tested.•The POx hydrogels exhibited good biocompatibility and magneto-mechanical activity.•The potential of prepared material is expected in biomechanics and biomedical field. Research on the subject of smart biomaterials has become a cornerstone of tissue engineering and regenerative medicine. Herein, the authors report on developing magnetic hydrogels that combine high biocompatibility and remarkable activity in magnetic fields. We fabricated magnetic hydrogels based on poly(2-ethyl-2-oxazoline) (POx) via living ring-opening cationic polymerization with in-situ embedding of the carbonyl iron (CI) particles. Investigation was made as to the effect exerted by the concentration of CI on magnetic, viscoelastic/magnetorheological properties, the degree of equilibrium swelling, and cytotoxicity. The hydrogels exhibited an open pore structure, as evidenced by computed tomography (CT) imaging. Susceptibility measurements revealed the concentration-dependent field-induced particle restructuration indicating elongation/contraction of the material, thereby determining the potential for magneto-mechanical stimulation of the cells. The POx-based magnetic hydrogels were amphiphilic in character, showing decrease in their capability to hold liquid alongside increase in CI concentration. Viscoelastic measurements suggested that interaction occurred between the particles and matrix based on inconsistency between the experimental storage modulus and the Krieger–Dougherty model. The synthesized materials exhibited excellent biocompatibility toward the 3T3 fibroblast cell line in tests of extract toxicity and direct contact cytotoxicity (ISO standards). The unique combination of properties exhibited by the material - magneto-mechanical activity and biocompatibility - could prove favorable in fields such as biomedicine and biomechanics.